Preparation of microencapsulated phase change materials (MEPCM) for thermal energy storage - Su, Weiguang; Darkwa, Jo; Kokogiannakis, Georgios; Zhou, Tongyu; Li, Yiling (Elsevier, 2017)
Microencapsulated phase change materials (MEPCM) could be used for energy saving applications in buildings due to their relatively high energy storage capacities at constant temperature, which could passively reduce peak cooling loads in summer. In this study, poly(methyl methacrylate-co-methacrylic acid) (PMMA-MAA) was used as a shell material to fabricate MEPCM by crosslinking methyl methacrylate (MMA) and methacrylic acid (MAA) through in-situ suspension-like polymerization method. The effects of initiator weight percentage and the ratio of shell monomers for the preparation of MEPCM were also investigated. The experimental results showed that the best MEPCM sample was achieved with a shell monomer weight ratio of 80% MMA : 20% MAA and thermal initiator of 1 wt%. Differential scanning calorimetric (DSC) analysis also showed a latent heat value for the best sample as 170 kJ/kg with a melting temperature of 23.68°C which makes these materials suitable for application in residential buildings. Meanwhile, the core material contents and encapsulation efficiencies were calculated according to the measured results of the DSC. Finally the thermogravimetric (TG) analysis on the samples showed very good thermal stability behaviours ranging between 162.3°C and 204.4°C and therefore satisfies the environmental requirements for most applications.